2004
DOI: 10.1111/j.1365-2044.2004.03834.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the transcription of laboratory data in an intensive care unit

Abstract: SummaryManual transcription of numerical data is prone to error. We quantified the transcription error rate for blood results recorded in a critical care setting by comparing the handwritten and printed laboratory results in 100 consecutive patients in the intensive care unit, Glasgow Royal Infirmary. Nine hundred and fifty-four sets of results with 4664 individual values were analysed. There was complete and accurate transcription in 67.6% (n = 645) of cases, a failure to transcribe in 23.6% (n = 225) and ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In the era of widespread electronic health record (EHR) use (13), clinicians perform much of the prerounding tasks of acquiring, collating, and processing patient data by directly interfacing with the EHR. EHR rounding widgets, data graphing tools, and macros that allow automatic data importation into progress notes can support more efficient data gathering (14) that is less prone to transcription errors of paper charting (15). Conversely, studies of EHR navigation from both real-world (16) and simulation-based (17) ICU settings demonstrate that chart review requires screen switching between over 25 unique screens, suggesting poor EHR usability and design as it relates to data retrieval for critically ill patients.…”
mentioning
confidence: 99%
“…In the era of widespread electronic health record (EHR) use (13), clinicians perform much of the prerounding tasks of acquiring, collating, and processing patient data by directly interfacing with the EHR. EHR rounding widgets, data graphing tools, and macros that allow automatic data importation into progress notes can support more efficient data gathering (14) that is less prone to transcription errors of paper charting (15). Conversely, studies of EHR navigation from both real-world (16) and simulation-based (17) ICU settings demonstrate that chart review requires screen switching between over 25 unique screens, suggesting poor EHR usability and design as it relates to data retrieval for critically ill patients.…”
mentioning
confidence: 99%
“…Electronic health records (EHRs) offer a data management solution by providing a central repository of categorized, legible data that can be accessed by multiple users simultaneously during ICU rounds (21). EHRs also support the creation of rounding tools, which through macros, can automatically populate data, saving time and eliminating transcription errors (22, 23). Unfortunately, EHR use has yet to consistently improve ICU outcomes, which may in part relate to problems with EHR implementation, novel patient safety issues created by the EHR, and suboptimal EHR design and usability (2427).…”
mentioning
confidence: 99%
“…This was consistent with our findings where time and day of presentation were not associated with documentation completeness. Conversely, another ICU study showed that transcription of laboratory results was more accurate when recorded in the morning …”
Section: Discussionmentioning
confidence: 97%